Notes on Research Methods - José Corona Lisboa (Medisur)
Since before the twentieth century or so, researchers have used various research methodologies supported by instruments that collect and measure the findings in its observations, experiences and experiments, in order to expose and publicize the scientific community and public overall, the conclusions reached in such investigations, based on objectives and results thereof. This review article discusses the research methods used in all the sciences, for the purpose of clarifying differences between them.